Mekanisme Pemakzulan (Impeachment) Presiden: Studi Pebandingan Negara Indonesia dan Brasil - Edi Prabowo (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
Impeachment is the process of dismissing a president from his position. In this case, Indonesia and Brazil are countries that adhere to a presidential system of government, and have dismissed the president, so it is interesting to study more closely the similarities and differences in the reasons a president can be impeached and the mechanism for impeachment of presidents in both countries. the. This study uses a normative juridical approach and with descriptive analysis research specifications. The data used is data in the form of secondary and tertiary materials collected by document study techniques. In this study the authors used qualitative data analysis methods. The collected data is then processed and arranged systematically for further descriptive presentation.Departing from a different constitutional system, the reasons and mechanisms for impeachment for the president are also different. Thereasons for the impeachment of the president must be in accordancewith the constitution as the highest law, where in Indonesia it is regulated in Article 7A of the 1945 NRI Constitution, while in Brazil it is regulated in Art. 85 Brazil's 1988 Constitution. The impeachment mechanism for the president in Indonesia involves 3 (three) state institutions, namely the House of Representatives (DPR), the Constitutional Court (MK) and the People's Consultative Assembly (MPR). The mechanism starts with the right to express an opinion by the DPR, then the opinion of the DPR is assessed by the Constitutional Court. If the Constitutional Court confirms the DPR's opinion, the decision is forwarded to the MPR to be brought to the Plenary Session. And in the trial the MPR decision was a political decision (politieke beslessing).Likewise, impeachment in Brazil involves 3 (three) state institutions, namely the Council of Deputies, the Supreme Court and the Senate. The mechanism starts from the initiation of the Council of Deputies, then the Council of Deputies to form a Congressional Committee to investigate, if it is justified it will be brought to full trial. The Council of Deputies is then brought before the Senate which has full authority, led by the Chief Justice of the Supreme Court. The results of the decisions of the Senate are semi-justicial decisions. The punishment of the impeachment decision in Indonesia is to stop serving as President while Brazil is to stop serving as president and the punishment for not serving as a public official for a period of 8 years. So that the difference between the two state mechanisms lies in the nature of the impeachment decision and the punishment of the impeachment decision.